2011
DOI: 10.1200/jco.2011.29.15_suppl.8031
|View full text |Cite
|
Sign up to set email alerts
|

Results from a pivotal phase II study of brentuximab vedotin (SGN-35) in patients with relapsed or refractory Hodgkin lymphoma (HL).

Abstract: Background: Relapsed/refractory (R/R) Hodgkin lymphoma (HL) remains a significant clinical challenge. We hypothesized that using an immune checkpoint inhibitor to activate the immune cells in the tumor microenvironment, and concurrently targeting tumor cells with the CD30 antibody-drug conjugate brentuximab vedotin (BV) could overcome resistance. E4412 is a Phase 1 ECOG-ACRIN sponsored study of the combinations of BV and ipilimumab (Ipi) and nivolumab (Nivo) in patients with R/R HL. Here we present the updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…Brentuximab vedotin (BV) is a CD30-directed antibody-drug conjugate consisting of the human CD30 antibody cAC10 and the microtubule-disrupting agent, monomethyl auristatin E (MMAE). BV is approved for the treatment of relapsed classical Hodgkin lymphoma 7 and systemic anaplastic large-cell lymphoma 8 and has also been preliminarily shown to be safe and effective for treatment of relapsed disease after allogeneic HCT. 9 Here, we report the results of a multicenter phase 1 study investigating BV for the treatment of SR-aGVHD.…”
Section: /Cd30mentioning
confidence: 99%
“…Brentuximab vedotin (BV) is a CD30-directed antibody-drug conjugate consisting of the human CD30 antibody cAC10 and the microtubule-disrupting agent, monomethyl auristatin E (MMAE). BV is approved for the treatment of relapsed classical Hodgkin lymphoma 7 and systemic anaplastic large-cell lymphoma 8 and has also been preliminarily shown to be safe and effective for treatment of relapsed disease after allogeneic HCT. 9 Here, we report the results of a multicenter phase 1 study investigating BV for the treatment of SR-aGVHD.…”
Section: /Cd30mentioning
confidence: 99%
“…Recently, brentuximab vedotin was approved for this specific patient population, but even with this active agent, median progression-free survival was approximately 6 months. 4 Patients who achieve adequate responses to post-ASCT salvage therapies are often referred for an allogenic stem-cell transplantation (alloSCT), which is associated with long-term remission rates ranging from 20% to 59%; however, minimal disease state at the time of transplantation is important for favorable outcome. [5][6][7] Bendamustine is a bifunctional alkylating agent with only partial cross resistance to other alkylating agents, making it an attractive agent for use in the relapsed setting.…”
Section: Introductionmentioning
confidence: 99%
“…A phase I, open-label trial in 42 HL patients who had failed a median of three previous chemotherapies, including 73% with prior ASCT, showed durable objective responses, with mild toxicity in the majority of patients [79]. Recently a pivotal phase II study confirmed the efficacy and safety of this agent in 102 patients with relapsed or refractory HL after ASCT [80]. An ongoing, randomized, placebo-controlled, multicenter phase III trial is evaluating the efficacy and safety of brentuximab vedotin in patients who have received ASCT in the previous 30 -45 days and are at high risk for residual HL post-ASCT, defined as those with a history of refractory disease who relapse or progress within 1 year from receiving frontline chemotherapy and those who have extranodal disease at the time of relapse (ClinicalTrials.gov identifier, NCT01100502).…”
Section: Role Of New Agents In Salvage Therapy and Hdtmentioning
confidence: 94%